2017
DOI: 10.2196/mhealth.9035
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Smoking Events Using Accelerometer Data Collected Via Smartwatch Technology: Validation Study

Abstract: BackgroundSmoking is the leading cause of preventable death in the world today. Ecological research on smoking in context currently relies on self-reported smoking behavior. Emerging smartwatch technology may more objectively measure smoking behavior by automatically detecting smoking sessions using robust machine learning models.ObjectiveThis study aimed to examine the feasibility of detecting smoking behavior using smartwatches. The second aim of this study was to compare the success of observing smoking beh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…It also allows for "in-time" intervention techniques to be developed. Our previous work [6] in this field has indicated that smoking can be detected using only accelerometer data and single-layer artificial neural networks (ANNs) with an accuracy of ~95% in laboratory settings and ~90% in real-world settings [6], [11]. Independent reports [12]- [16] also confirmed the usability of smartwatches in the study of human behavior.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…It also allows for "in-time" intervention techniques to be developed. Our previous work [6] in this field has indicated that smoking can be detected using only accelerometer data and single-layer artificial neural networks (ANNs) with an accuracy of ~95% in laboratory settings and ~90% in real-world settings [6], [11]. Independent reports [12]- [16] also confirmed the usability of smartwatches in the study of human behavior.…”
Section: Introductionmentioning
confidence: 87%
“…Smartwatches have been used as stepcounters [16], sleep monitoring [18], diet monitoring [13] as well as general fitness tracking [19]. In the context of smoking, smartwatches have demonstrated to be usable for in-situ study of smoking [20], [21] with high accuracy [6], [20]- [22]. Smartwatches have been used to detect smoking gesture with 95% accuracy in laboratory environment [23] and 90% in-situ detection of smoking [6].…”
Section: A Previous and Related Workmentioning
confidence: 99%
See 3 more Smart Citations